(untitled) (Revista Electrónica Calidad en la Educación Superior, 2025)
Administrative theory, specifically the Administrative Process, is the reference to satisfy the needs of organizations in their managerial practice to achieve objectives; its application in both public and private health services is no exception. Academic training in areas such as administrative, hospital, and public health management benefits from integrating real-life case studies that allow students to develop planning, organizational, and management skills in professional contexts. This paper conducts a comparative analysis, using a SWOT analysis, between the administrative management implemented for the establishment of a private therapeutic practice and the administrative theory applied to health services. Those managing a private health service provider organization must be capable of planning, organizing, directing, and controlling; that is, they must be able to apply the administrative process from a health services perspective. This will support the innovative and entrepreneurial ideas that led them to create their own company, with a view to achieving their objectives. Knowledge of administrative theory applied to health services is a fundamental tool that everyone who manages a private service must implement, seeking efficiency through the recognition and description of their environment, identifying the opportunities and threats they find, and addressing their weaknesses and enhancing their strengths, all without losing sight of the essence of achieving their objectives and goals. This type of research facilitates the understanding of administrative principles applied to the development of therapeutic spaces, providing future professionals with concrete tools for making decisions based on theory and practice.